Social Health in the Context of Phenomenological Risks - Lyudmila KILIMOVA; Michail CHERKASHIN; Olga NISHNIANIDZE (Communications of International Proceedings, 2020)
The article defines the essence and content of social health. It has been shown that reproduction of health reflects birth process of healthy generation, the basis of which is a full-fledged set of genes and hereditary factor. Health preservation is not only a biological problem. Health is directly related to the level, mode and quality of life of each person and the population of the country as a whole.
Keywords: Social Health; Social Risks; Human Capital; Pandemic; Coronavirus.